2021
DOI: 10.3389/fpls.2021.776816
|View full text |Cite
|
Sign up to set email alerts
|

PpMYB36 Encodes a MYB-Type Transcription Factor That Is Involved in Russet Skin Coloration in Pear (Pyrus pyrifolia)

Abstract: Fruit color is one of the most important external qualities of pear (Pyrus pyrifolia) fruits. However, the mechanisms that control russet skin coloration in pear have not been well characterized. Here, we explored the molecular mechanisms that determine the russet skin trait in pear using the F1 population derived from a cross between russet skin (‘Niitaka’) and non-russet skin (‘Dangshansu’) cultivars. Pigment measurements indicated that the lignin content in the skin of the russet pear fruits was greater tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 53 publications
(57 reference statements)
0
8
0
Order By: Relevance
“…In plants, various MYB transcription factors regulate either suberin biosynthesis or extracellular lipid accumulation. In pears, 12 MYB genes involved in plant tissue suberization were differentially upregulated in the russet fruit skin, indicating that these MYB genes may affect russeting formation by regulating suberin synthesis ( Ma et al., 2021 ). In addition, MYB9 and MYB107 ( Lashbrooke et al., 2016 ), MYB6 and MYB67 ( Falginella et al., 2021 ), and MYB93 ( Legay et al., 2016 ) involvement has been reported in suberin in fruit russeting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In plants, various MYB transcription factors regulate either suberin biosynthesis or extracellular lipid accumulation. In pears, 12 MYB genes involved in plant tissue suberization were differentially upregulated in the russet fruit skin, indicating that these MYB genes may affect russeting formation by regulating suberin synthesis ( Ma et al., 2021 ). In addition, MYB9 and MYB107 ( Lashbrooke et al., 2016 ), MYB6 and MYB67 ( Falginella et al., 2021 ), and MYB93 ( Legay et al., 2016 ) involvement has been reported in suberin in fruit russeting.…”
Section: Discussionmentioning
confidence: 99%
“…The main effector gene controlling russet variation in ‘Renetta Grigia di Torriana’ apples is located on chromosome LG12 ( Falginella et al., 2015 ). The PpRus gene, which controls the pear russet skin trait, was identified via Bulked Segregant analysis and is located on chromosome 8 of the pear genome ( Ma et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…QTL analysis of this population showed that russeting loci were located on Chr 3, 19, and 23 ( Macnee et al, 2021 ). In a recent study, BSA-seq (RNA-seq-based bulked segregant analysis) was performed, in which linkage analysis found that the PpRus locus is located on Chr 8 ( Ma et al, 2021 ). As these results indicate that hybrid groups are appropriate materials to study russeting in fruit tree, they may provide more unique phenotypes for further study.…”
Section: Genetics and Regulation Of Fruit Russetingmentioning
confidence: 99%
“…In pear, transient expression of PbHHT1 gene in young green non-russet fruits led to a lenticel suberization genotype with higher content of ω-feruloyloxypalmitic acid ( Shi et al, 2021 ). Using BSA-seq, a MYB transcription factor MYB36 was identified as a regulator that was involved in lignin accumulation and russet coloration in pear ( Ma et al, 2021 ). In addition to the above genes, ABCGs were also involved in suberin formation and fruit russeting ( Falginella et al, 2015 ; Hou et al, 2018 ; Shi et al, 2021 ), but the functions of this family remain to be determined in fruit tree.…”
Section: Genetics and Regulation Of Fruit Russetingmentioning
confidence: 99%
See 1 more Smart Citation